Analysis of the Discovery Learning Model in Improving Student Learning Outcomes at State Senior High School 12 Padang - Hisnil Khotimah L; Clara Septiarama; Yuliawati Yunus (Global Education Journal, 2025)
This study aims to determine the effectiveness of the Discovery Learning learning model in improving student learning outcomes at SMA Negeri 12 Padang. The Discovery Learning learning method, which begins with students' independent discovery of concepts, can improve motivation, understanding, and critical thinking skills. This study uses a quantitative approach with a quasi-experimental design involving Phase F students at SMA Negeri 12 Padang. Student learning outcome data were collected through pre-tests and post-tests, then analyzed using an independent t-test to determine significant differences between the group implementing the Discovery Learning model and the control group using conventional methods. A questionnaire was also used to measure students' perceptions of the learning experience. The results showed that there was a significant increase in student learning outcomes using the Discover Learning model compared to the control group. This increase was seen in students' abilities to understand complex concepts, problem-solving abilities, and critical thinking abilities. The implication of this finding is that Discovery Learning can be an effective alternative to improve the quality of more effective learning, as well as providing insight for teachers in designing more interesting and relevant learning for students.